2019
DOI: 10.1111/tpj.14454
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic diversification of nitrogen‐containing metabolites by the expression of a heterologous lysine decarboxylase gene in Arabidopsis

Abstract: Summary Lysine decarboxylase converts l‐lysine to cadaverine as a branching point for the biosynthesis of plant Lys‐derived alkaloids. Although cadaverine contributes towards the biosynthesis of Lys‐derived alkaloids, its catabolism, including metabolic intermediates and the enzymes involved, is not known. Here, we generated transgenic Arabidopsis lines by expressing an exogenous lysine/ornithine decarboxylase gene from Lupinus angustifolius (La‐L/ODC) and identified cadaverine‐derived metabolites as the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The evolution of a specialized metabolite biosynthetic pathway involves the emergence of enzymes that catalyze committed steps toward synthesizing core metabolites. These core metabolites are then subsequently catalyzed by native coopting enzymes, resulting in the colossal chemodiversity of the plant metabolome 51 , 52 . The expanded chemodiversity, upon serving as a positive selection force, activates the evolutionary machinery, including the emergence of novel specialized enzymes through gene expansion/neofunctionalization, thus beginning the process of refining the imperfect secondary metabolite biosynthesis pathways 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of a specialized metabolite biosynthetic pathway involves the emergence of enzymes that catalyze committed steps toward synthesizing core metabolites. These core metabolites are then subsequently catalyzed by native coopting enzymes, resulting in the colossal chemodiversity of the plant metabolome 51 , 52 . The expanded chemodiversity, upon serving as a positive selection force, activates the evolutionary machinery, including the emergence of novel specialized enzymes through gene expansion/neofunctionalization, thus beginning the process of refining the imperfect secondary metabolite biosynthesis pathways 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results identified a shared WGD event across papilionoids in G. uralensis genome, with more than half of the genes identified as orthologous (two to five-membered orthogene families), supporting the role of the neofunctionalization hypothesis for specialized metabolite biosynthesis driven by locally duplicated or rearranged genes. 75 , 84 …”
Section: Resultsmentioning
confidence: 99%
“…202 By expressing a bifunctional lysine/ornithine decarboxylase enzyme, L/ODC, in Arabidopsis, Shimizu et al showed the emergence of non-native specialized metabolites, including alkaloid-like metabolites. 203 The authors used the core chemical structure of cadaverine to identify the metabolic intermediates and enzymes involved in articially established chemodiversity in Arabidopsis; they demonstrated the role of promiscuous enzymes in deriving the metabolite diversity and described the emergence of metabolite scaffolds as the key event.…”
Section: Comparative Genomics and Phylogenetic Approaches To Elucidate The Metabolites' Diversity And Role In Speciationmentioning
confidence: 99%